2003
DOI: 10.1034/j.1600-0528.2003.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoridated milk on caries in primary teeth: 21‐month results

Abstract: The consumption of fluoridated milk by the kindergarten children in Beijing was an effective measure in preventing caries in the primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
0
16
0
6
Order By: Relevance
“…The use of fluoridated water when reconstituting powdered infant formula influences cariogenic properties of the formula (Bian, Wang, Wang, Rong, & Lo, 2009). In a desalivated rat model, total smooth surface and sulcal caries scores were lower for bovine milk, human milk, and an infant formula supplemented with 10 ppm fluoride than sucrose (5%) and non-fortified (reconstituted with sterile, distilled water) infant formula (Peres et al, 2009).…”
Section: Infant Formulamentioning
confidence: 99%
“…The use of fluoridated water when reconstituting powdered infant formula influences cariogenic properties of the formula (Bian, Wang, Wang, Rong, & Lo, 2009). In a desalivated rat model, total smooth surface and sulcal caries scores were lower for bovine milk, human milk, and an infant formula supplemented with 10 ppm fluoride than sucrose (5%) and non-fortified (reconstituted with sterile, distilled water) infant formula (Peres et al, 2009).…”
Section: Infant Formulamentioning
confidence: 99%
“…13 Whilst a recent systematic review suggested better quality research is needed regarding the effectiveness of milk fluoridation, 9 a number of trials across the world have shown it to be effective in reducing the prevalence of dental caries in children. For example trials in Chile, [14][15][16] Bulgaria, 17,18 China, 19 Sweden 20 and England 21 have shown that children who participated in the fluoridated milk programme experienced significantly less dental caries compared to children not on the programme. Adding fluoride to the milk-products as part of a National Food Supplement Programme has been found to be cost-effective in rural areas of Chile.…”
Section: Re-mineralizationmentioning
confidence: 99%
“…Interesting initiatives such as sending school milk home on a Friday evening for consumption over the weekend have been reported in China, where milk consumption has been maintained for more than 300 days per year. 49 To date no milk fluoridation programmes have been targeted at and evaluated in adult populations. Still today, WHO is involved in comprehensive milk fluoridation programmes in several countries such as Thailand and Bulgaria.…”
Section: Milk Fluoridationmentioning
confidence: 99%